High performance zirconia ceramic particles and methods for making the same

CN122562504BActive Publication Date: 2026-10-27YIYANG JINNENG NEW MATERIAL
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202611072339.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-27
Estimated Expiration
2046-07-20

AI Technical Summary

Technical Problem

这种“均匀复合”思路导致了三个无法回避的困境:其一,高硬度与高韧性、高强度与良好润湿性在单一材料体系中往往此消彼长,均匀结构只能让性能相互妥协;其二,为实现界面结合等功能而添加的昂贵组分,被浪费在对该功能需求不高的颗粒内部,导致性价比不高;其三,不同材料的热膨胀系数和弹性模量差异巨大,均匀混合后在烧结和使用过程中容易产生热应力,成为微裂纹萌生的潜在源头

Benefits of technology

梯度结构带来的性能突破:本发明通过构建“高强内核-过渡层-富韧表层”的梯度结构,使陶瓷颗粒内部高硬度与表层高韧性得以兼得,克服了传统均匀结构只能性能折中的缺陷。过渡层有效缓解了内核与表层之间的热膨胀系数失配,消除了界面应力,避免了微裂纹的产生。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122562504B_ABST
    Figure CN122562504B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of ceramic material preparation, and particularly discloses high-performance zirconia ceramic particles and a preparation method thereof, the ceramic particles have a composition gradient structure which is sequentially rich in a tough surface layer, a transition layer and a high-strength inner core from outside to inside; the preparation method comprises the following steps: respectively preparing an inner core slurry and a surface layer slurry containing silicides; adopting a gradient granulation process, first granulating the inner core slurry to form an inner core green body, then gradually increasing the surface layer slurry to make the particles grow to a target size, and drying and screening to obtain green body particles; then sequentially performing first-step sintering at 1450-1550 DEG C under an air atmosphere and second-step sintering at 1200-1350 DEG C under vacuum or an inert atmosphere. The application realizes the synergistic improvement of high inner core hardness and high surface layer toughness through the gradient structure, and improves the wettability with a metal matrix, and is suitable for a wear-resistant composite material reinforcing body.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of ceramic material preparation technology, specifically relating to a high-performance zirconia ceramic particle and its preparation method. Background Technology

[0002] Ceramic particles are widely used as grinding media, sandblasting materials, and reinforcements in metal matrix composites due to their high hardness, good chemical stability, and wear resistance. Among them, zirconia (ZrO2)-based and alumina-zirconia (ZTA) multiphase ceramics are the preferred materials in the field of wear-resistant particles.

[0003] To pursue superior performance, existing technologies have undergone extensive research. For example, the "simple multiphase conversion" technology route, represented by patents CN106187179A and CN106242565A, introduces stabilized ZrO2 into Al2O3, utilizing the phase transformation toughening mechanism of ZrO2 to compensate for the brittleness of Al2O3, thereby achieving higher fracture toughness than single Al2O3 ceramics. This type of technology typically uses isostatic pressing or electrofusion processes to prepare uniformly composed ceramic particles, and uses a crushing process to obtain a rough particle morphology to enhance the mechanical bonding force with the metal matrix. However, this uniform structure cannot simultaneously address the differentiated performance requirements of different parts of the particle—the particle surface requires high toughness and good chemical affinity when composited with metal, while the particle core requires extremely high hardness and crushing strength. A uniform structure can only be a performance "compromise," and due to the inherent differences in physicochemical properties between ceramics and metals, the wettability remains poor during high-temperature casting, easily leading to defects such as porosity and inclusions at the composite material interface. To address the aforementioned interface issues, another type of "interface functionalization" technology has emerged, typically represented by patents CN117125960B and CN117142840A. The core innovation of this technology lies in introducing high-melting-point carbides such as Cr3C2 or TiC into the Al2O3 matrix. Utilizing the excellent wettability of these carbides with molten iron, the metal is encouraged to penetrate the ceramic particle preform during casting, resulting in a dense, defect-free composite material. This is a "systematic" optimization approach that links the properties of the ceramic particles themselves with their behavior in the composite material, and experiments have proven its effectiveness in improving interfacial bonding. However, this technology also has significant drawbacks. For example, the raw material prices of Cr3C2 and TiC are much higher than those of Al2O3 and ordinary ZrO2, leading to a substantial increase in material costs. Furthermore, this approach focuses on "wettability," offering limited contribution to improving the intrinsic wear resistance properties of the ceramic particles, such as hardness and fracture toughness. Additionally, the large addition of carbides may affect the phase transformation toughening effect of ZrO2. More importantly, similar to the first type of technology, the functional phase is also uniformly distributed in the particles. The high-cost functional phase is not only distributed on the surface where it is needed, but also in the interior where it is not needed, resulting in a certain waste of resources.

[0004] In summary, existing technologies for processing high-performance wear-resistant ceramic particles generally suffer from a common mindset and technical limitation: the adoption of a "homogeneous composite" approach, attempting to satisfy all performance requirements with a fixed composition. This "homogeneous composite" approach leads to three unavoidable dilemmas: First, high hardness and high toughness, high strength and good wettability often come at a trade-off in a single material system, and a homogeneous structure only allows for compromises in performance; second, expensive components added to achieve functions such as interfacial bonding are wasted within particles with low demand for these functions, resulting in low cost-effectiveness; third, the significant differences in the coefficients of thermal expansion and elastic modulus of different materials can easily generate thermal stress during sintering and use after homogeneous mixing, becoming a potential source of microcrack initiation. Therefore, how to break through the traditional framework of "homogeneous composite" and design a new structure that allows each part of the ceramic particle to "perform its own function and synergistically enhance each other," and realize this through a low-cost, high-efficiency process, has become a pressing technical challenge in this field. Summary of the Invention

[0005] To address the shortcomings of existing wear-resistant ceramic particles in simultaneously achieving high surface toughness, high core hardness, and excellent interfacial bonding performance, this invention provides a high-performance zirconia ceramic particle with a "core-transition layer-surface layer" gradient structure and its preparation method, achieving a coordinated balance of high core strength, high surface toughness, excellent interfacial bonding, and controllable cost.

[0006] The present invention first provides a high-performance zirconia ceramic particle, wherein the ceramic particle has a compositional gradient structure consisting of a tough surface layer, a transition layer and a high-strength core layer from the outside to the inside.

[0007] The high-strength core comprises, by weight percentage, 40-70% Al2O3, 30-60% 3 mol% yttrium oxide-stabilized zirconium oxide (3Y-ZrO2), and 0.1-5% sintering aids; the sintering aids are selected from at least one of TiO2 and MgO.

[0008] The toughened surface layer, by weight percentage, comprises 60-90% 3 mol% yttrium-stabilized zirconium oxide, 10-40% Al2O3, and 0.5-5% silicide; the silicide is uniformly dispersed in the toughened surface layer, and the silicide is selected from at least one of molybdenum silicide and zirconium silicide.

[0009] The toughened surface layer further comprises 0.2-5% of a grain growth inhibitor, wherein the grain growth inhibitor is selected from at least one of CeO2 and Y2O3.

[0010] The composition of the transition layer is between the high-strength core and the tough surface layer, exhibiting a continuous gradient change.

[0011] The high-strength core layer has a relatively high Al2O3 content, forming a high-hardness corundum skeleton that provides core support and crush resistance. The transition layer has a composition between the high-strength core and the tough surface layer. This layer effectively alleviates the mismatch in thermal expansion coefficient and elastic modulus between the core and the surface layer through compositional gradient, eliminating interfacial stress. The tough surface layer utilizes a high content of 3Y-ZrO2 to provide excellent fracture toughness. The dispersed silicides can significantly improve the wettability of ceramics and metal melts when combined with a metal matrix, or enhance interfacial bonding when combined with a resin matrix.

[0012] This invention also provides a method for preparing the above-mentioned high-performance zirconia ceramic particles, the method comprising the following steps: S1. Preparing the powder: According to the above-mentioned component ratio of high-strength core and tough surface layer, the raw materials were weighed separately. The core slurry was made by ball milling Al2O3, 3 mol% yttrium oxide-stabilized zirconium oxide, sintering aid, dispersant, binder and water; the surface slurry was made by ball milling 3 mol% yttrium oxide-stabilized zirconium oxide, Al2O3, silicide or silicide precursor, grain growth inhibitor, dispersant, binder and water. S2, gradient granulation: Using a granulator, the core slurry obtained in step S1 is first granulated to form a core green body. Then, during the granulation process, the amount of core slurry added is gradually reduced while the amount of surface slurry added is gradually increased. Granulation continues until the target size is reached. After drying and sieving, green body particles with composition gradient are obtained. S3, single sintering: The green pellets obtained in step S2 are sintered in air atmosphere at a temperature of 1450~1550℃ and a holding time of 1~3 hours to densify the green pellets and form a composition gradient. S4, Secondary sintering: The particles obtained in step S3 are sintered in a second step under vacuum or inert atmosphere at a sintering temperature of 1200~1350℃ and a holding time of 0.5~2 hours to obtain the high-performance zirconia ceramic particles.

[0013] If the secondary sintering temperature is below 1200℃, the thermal stress generated by the primary sintering cannot be effectively eliminated, and the surface toughness of the particles is not significantly improved; if it is above 1350℃, it will lead to excessive growth of ZrO2 grains, which will reduce the fracture toughness.

[0014] Preferably, the silicide precursor in step S1 is molybdenum silicide powder or zirconium silicide powder.

[0015] Preferably, the granulator in step S2 is a disc granulator or a fluidized bed granulator.

[0016] Preferably, in step S2, the feeding ratio of the core slurry to the surface slurry is adjusted from 10:0 to 0:10 within 15 to 30 minutes to form a transition layer with continuously changing composition.

[0017] Preferably, the heating rates for the primary sintering in step S3 and the secondary sintering in step S4 are independently 2~5℃ / min.

[0018] Compared with the prior art, the beneficial effects of the present invention are: Performance Breakthrough Brought by Gradient Structure: This invention achieves a balance between high hardness inside the ceramic particles and high toughness on the surface by constructing a gradient structure of "high-strength core - transition layer - tough surface," overcoming the shortcomings of traditional uniform structures that can only compromise performance. The transition layer effectively alleviates the mismatch in thermal expansion coefficients between the core and the surface, eliminates interfacial stress, and avoids the generation of microcracks.

[0019] Optimized balance between function and cost: High-cost silicide functional components are concentrated only in the surface layer where wettability improvement is needed, while the core uses lower-cost Al2O3 and a suitable amount of ZrO2. Compared with homogeneous multiphase ceramics with overall carbide addition, this invention significantly reduces material costs while ensuring excellent interfacial bonding performance.

[0020] The process is simple and feasible: it adopts the process route of "gradient granulation + two-step sintering", which can be realized based on mature ceramic processing equipment. It does not require complicated coating or coating processes and is easy to industrialize. Attached Figure Description

[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0022] Figure 1 This is a flowchart illustrating the preparation process of ceramic particles according to the present invention. Figure 2 This is a photograph of the morphology of ceramic particles prepared in Example 1 of the present invention. Detailed Implementation

[0023] The following embodiments are used to illustrate the present invention, but are not intended to limit the scope of the invention. Any modifications or substitutions made to the methods, steps, or conditions of the present invention without departing from the spirit and essence of the invention are within the scope of the invention. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art.

[0024] Example 1

[0025] This embodiment is used to prepare high-performance zirconia ceramic particles with a target particle size of 0.8-1.2 mm.

[0026] (1) Powder preparation: Core material preparation: Weigh 60 parts by weight of Al2O3, 35 parts by weight of 3 mol% yttrium oxide-stabilized zirconium oxide, and 5 parts by weight of TiO2 as sintering aids. Add 0.5 parts by weight of polyvinyl alcohol as a binder, 0.2 parts by weight of ammonium polyacrylate as a dispersant, and deionized water as the ball milling medium to the above mixed powder. Mix the above raw materials in a ball mill for 8 hours to obtain a core slurry with a solid content of 65%.

[0027] Preparation of the surface layer material: Weigh out 20 parts by weight of Al2O3, 75 parts by weight of 3 mol% yttrium oxide-stabilized zirconium oxide, 5 parts by weight of MoSi2 powder, and 1 part by weight of CeO2 as a grain growth inhibitor. Using the same method as the core material, add binder, dispersant, and deionized water, and ball mill for 8 hours to obtain a surface layer slurry with a solid content of 65%.

[0028] (2) Gradient granulation: Gradient granulation was performed using a disc granulator at a speed of 40 rpm. First, core slurry was intermittently sprayed into the center of the granulation pan, producing spherical core preforms with a particle size of approximately 0.4 mm. Maintaining a constant total slurry volume, the feed ratio of core slurry to surface slurry was linearly adjusted from 10:0 to 0:10 over 20 minutes. During this process, the particle diameter continuously increased until it reached 0.9-1.3 mm. After granulation was stopped, the resulting wet granules were removed and dried in a 110℃ oven for 12 hours. They were then sieved to obtain green preforms with a compositional gradient and a particle size of 0.8-1.2 mm.

[0029] (3) Single sintering: The green pellets were placed in a corundum crucible and then placed in a box-type resistance furnace for sintering in air. The temperature was increased to 1500°C at a rate of 3°C / min, held for 2 hours, and then cooled to room temperature in the furnace. This step densifies the green pellets and creates a compositional gradient.

[0030] (4) Secondary sintering: The sintered particles were transferred to a vacuum furnace, where the vacuum level was controlled below 10 Pa. The temperature was increased to 1300℃ at a rate of 5℃ / min, held for 1 hour, and then cooled to room temperature in the furnace.

[0031] (5) Post-processing: After cooling, the ceramic particles are removed and sieved using a standard sieve to obtain high-performance zirconia ceramic particles with a particle size of 0.8-1.2 mm.

[0032] Example 2

[0033] The preparation method in this embodiment is basically the same as that in Example 1, except that: (1) Powder preparation: In the preparation of the surface material, 5 parts of MoSi2 powder were replaced with 5 parts of ZrSi2 powder.

[0034] (4) Secondary sintering: The temperature for the second sintering was adjusted to 1250℃, and the holding time was adjusted to 1.5 hours.

[0035] The remaining steps and parameters are the same as in Example 1, and will not be described again here.

[0036] Comparative Example 1 This comparative example is used to compare the performance of the ceramic particles with the gradient structure of the present invention, and to prepare a zirconia ceramic particle with uniform composition.

[0037] (1) Powder preparation: Based on the overall average composition, 40 parts by weight of Al2O3, 55 parts by weight of 3 mol% yttrium oxide-stabilized zirconium oxide, and 5 parts by weight of MoSi2 powder were weighed. Polyvinyl alcohol, ammonium polyacrylate, and deionized water were added in the same proportions as in Example 1, and the mixture was ball-milled for 8 hours to obtain a homogeneous slurry with a solid content of 65%.

[0038] (2) Granulation: Using the same disc granulator as in Example 1, the above-mentioned uniform slurry was directly rolled into wet granules with a particle size of 0.8-1.2 mm, and then dried in an oven at 110°C for 12 hours.

[0039] (3) Sintering: The same two-step sintering process as in Example 1 was adopted, namely, first heating to 1500°C at 3°C / min and holding for 2 hours in air atmosphere, and then heating to 1300°C at 5°C / min and holding for 1 hour in vacuum.

[0040] (4) Post-processing: After cooling, the ceramic particles are removed and sieved to obtain a finished product with a particle size of 0.8-1.2 mm.

[0041] Comparative Example 2 This comparative example is used to compare the performance with existing conventional technologies to prepare a conventional ZTA ceramic particle that does not contain silicon compounds.

[0042] (1) Powder preparation: Weigh out 50 parts by weight of Al2O3 and 50 parts by weight of 3 mol% yttrium oxide-stabilized zirconium oxide. Add polyvinyl alcohol, ammonium polyacrylate and deionized water in the same proportions as in Example 1, and ball mill to mix evenly to obtain a ZTA slurry with a solid content of 65%.

[0043] (2) Granulation: Using the same disc granulator as in Example 1, the above ZTA slurry was directly rolled into wet granules with a particle size of 0.8-1.2 mm, and then dried in an oven at 110°C for 12 hours.

[0044] (3) Sintering: The next sintering step is carried out in an air atmosphere, with the temperature increased to 1500°C at a heating rate of 3°C / min, held at that temperature for 2 hours, and then cooled to room temperature in the furnace.

[0045] (4) Post-processing: After cooling, the ceramic particles are removed and sieved to obtain ZTA ceramic particles with a particle size of 0.8-1.2 mm.

[0046] The ceramic particles prepared in Examples 1-2 and Comparative Examples 1-2 were subjected to performance tests. The test samples were all selected from particles with a particle size of 0.9-1.0 mm.

[0047] (1) Test method: The hardness test involved embedding ceramic particles and polishing them. A Vickers hardness tester was used to measure the hardness of the surface and central areas of the particles, with a test load of 1 kgf.

[0048] Fracture toughness was measured and calculated using the indentation method on the surface of polished particles, and the fracture toughness of the surface area and the central area were tested separately.

[0049] The crushing force test involves using a universal testing machine to compress individual ceramic particles and recording the maximum pressure value when the particle breaks.

[0050] The wettability test with metal involves placing ceramic particles in molten high-chromium cast iron at 1520℃, holding it at that temperature for 30 minutes, then removing and cooling it. The interface bonding between the particles and the metal is then observed, and the wettability level is judged according to the degree of bonding density.

[0051] The wear resistance test of the composite material involved preparing a high-chromium cast iron-based composite material sample with a particle volume fraction of 40% ceramic particles. Impact wear performance was tested on an MLD-10 dynamic load abrasive wear testing machine with an impact energy of 2.5 J and quartz sand as the abrasive. The wear amount of the high-chromium cast iron base material was measured under the same conditions, and the relative wear resistance was calculated as the ratio of the composite material wear amount to the cast iron base material wear amount.

[0052] (2) Test results: The test results of the examples and comparative examples are shown in Table 1.

[0053] Table 1 Tests of Examples and Comparative Examples

[0054] (3) Results analysis: The test results show that the gradient-structured ceramic particles prepared in Examples 1 and 2 exhibit a surface strength of 8.2-8.5 MPa·m due to the high content of 3 mol% yttrium oxide-stabilized zirconium oxide. 1 / 2 The high fracture toughness and the high hardness of 1510-1520 HV1 in the center due to the high Al2O3 content successfully achieve a gradient structure of "tough on the outside and hard on the inside". The addition of MoSi2 or ZrSi2 in the surface layer makes the wettability of ceramic particles with high chromium cast iron reach a good level, and the crushing force of individual particles and the relative wear resistance of composite materials are significantly better than those of the two comparative examples.

[0055] Although Comparative Example 1 has a uniform composition and contains MoSi2, and its wettability and surface hardness are acceptable, its overall toughness is not as good as the zirconium oxide-enriched surface layer of the present invention, and its central hardness is lower than that of the Al2O3-enriched core of the present invention, resulting in a significant decrease in crush resistance and wear resistance.

[0056] Comparative Example 2 uses conventional ZTA particles without silicon compounds, which have poor wettability with molten iron. This results in weak interfacial bonding of the composite material during wear, making the ceramic particles prone to detachment and leading to the lowest relative wear resistance. Its surface toughness is also lower than that of the embodiments of the present invention, and its impact resistance is relatively insufficient.

[0057] Although the present invention has been described in detail above with general descriptions and specific embodiments, modifications or improvements can be made to it, which will be obvious to those skilled in the art. Therefore, all such modifications or improvements made without departing from the spirit of the present invention fall within the scope of protection claimed by the present invention.

Claims

1. A high-performance zirconia ceramic particle, characterized in that, The ceramic particles have a compositional gradient structure consisting of a tough surface layer, a transition layer, and a high-strength core, from the outside in. The high-strength core, by weight percentage, comprises 40-70% Al2O3, 30-60% 3 mol% yttrium oxide-stabilized zirconium oxide, and 0.1-5% sintering aids; the sintering aids are selected from at least one of TiO2 and MgO. The toughened surface layer, by weight percentage, comprises 60-90% 3 mol% yttrium-stabilized zirconium oxide, 10-40% Al₂O₃, and 0.5-5% silicide; the silicide is uniformly dispersed in the toughened surface layer; the silicide is selected from at least one of molybdenum silicide and zirconium silicide; the toughened surface layer contains 0.2-5% grain growth inhibitor, the grain growth inhibitor being selected from at least one of CeO₂ and Y₂O₃; The composition of the transition layer is between the high-strength core and the tough surface layer, exhibiting a continuous gradient change.

2. A method for preparing the high-performance zirconia ceramic particles of claim 1, characterized in that, Includes the following steps: S1. Preparation of powder materials: According to the component ratio of the high-strength core and the tough surface layer as described in claim 1, the raw materials are weighed respectively. The core slurry is prepared by ball milling Al2O3, 3 mol% yttrium oxide-stabilized zirconium oxide, sintering aid, dispersant, binder and water; the surface slurry is prepared by ball milling 3 mol% yttrium oxide-stabilized zirconium oxide, Al2O3, silicide or silicide precursor, grain growth inhibitor, dispersant, binder and water. S2. Gradient Granulation: Using a granulator, the core slurry obtained in step one is first granulated to form a core green body. Then, during the granulation process, the amount of core slurry added is gradually reduced while the amount of surface slurry added is gradually increased. Granulation continues until the target size is reached. After drying and sieving, green body particles with a compositional gradient are obtained. In step S2, the feeding ratio of core slurry to surface slurry is adjusted from 10:0 to 0:10 within 15-30 minutes to form a transition layer with continuously changing composition. S3. First sintering: The green pellets obtained in step S2 are sintered in air atmosphere at a temperature of 1450-1550℃ and a holding time of 1-3 hours to densify the green pellets and form a composition gradient. S4. Secondary sintering: The particles obtained in step S3 are sintered under vacuum or inert atmosphere at a sintering temperature of 1200-1350℃ and a holding time of 0.5-2 hours to obtain the high-performance zirconia ceramic particles. The heating rate of the primary sintering and the secondary sintering is independently 2-5℃ / min.

3. The preparation method according to claim 2, characterized in that, The silicide is molybdenum silicide powder or zirconium silicide powder.

4. The preparation method according to claim 2, characterized in that, The granulator is a disc granulator or a fluidized bed granulator.

Citation Information

Patent Citations

  • Wear-resisting ZrO2-Al2O3 multiphase ceramic particles and preparation method and application thereof

    CN106187179A

  • Wear-resistant ZrO2-Al2O3 complex phase ceramic particles, preparation method and applications thereof

    CN106242565A

  • A method for preparing Al2O3 / Cr3C2 composite ceramic particles

    CN117125960B

  • Preparation method of Al2O3 / TiC composite ceramic particles

    CN117142840A

  • Preparation method of whisker toughened zirconia ceramic

    CN115010487A